Impact of skeletal maturation on bone metabolism biomarkers and bone mineral density in healthy Brazilian male adolescents - Silva, Carla C.; Goldberg, Tamara Beres Lederer [UNESP]; Nga, Hong S. [UNESP]; Kurokawa, Cilmery S. [UNESP]; Capela, Renata C. [UNESP]; Teixeira, Altamir S. [UNESP]; Dalmas, José C. (Fundacao Sociedade Brasileira de Pediatria, 2011)
Objective: To evaluate the behavior of biomarkers of bone formation and resorption in healthy male Brazilian adolescents according to their biological maturation. Methods: Eighty-seven volunteers were divided into age groups according to bone age (BA): 10-12 years (n = 25), 13-15 years (n = 36), and 16-18 years (n = 26). Weight (kg), height (m), body mass index (kg/m 2), calcium intake from 3 days assessed by 24-h food recall (mg/day), pubertal event evaluation by Tanner criteria, and serum biomarker levels (osteocalcin [OC] [ng/mL], bone alkaline phosphatase [BAP] [U/L], and serum carboxyterminal telopeptide [S-CTx] [ng/mL]) were recorded and correlated to bone mineral density (BMD) (g/cm 2) measured by dual energy X ray absorptiometry of the lumbar spine, proximal femur, and whole body. Results: Biomarkers showed similar behaviors, presenting higher median values in the 13-15 year group (BAP = 154.71 U/L, OC = 43.0 ng/mL, S-CTx = 2.09 ng/mL; p < 0.01) and when adolescents were in the pubertal stage G4. Median biomarker values decreased with advancing BA and sexual maturation. Biomarker values showed parallelism with peak height velocity, and, interestingly, bone formation biomarkers indicated significant negative correlation with BMD in the different evaluated locations, i.e., higher BMD values correlated with lower bone biomarker values. Conclusions: This is the first study of healthy Brazilian adolescents with rigid and careful inclusion and exclusion criteria to assess the correlation of bone markers and BMD with biological maturation indicators. Our results can help understand bone turnover and monitor bone metabolism. Copyright © 2011 by Sociedade Brasileira de Pediatria.
Keywords: Adolescents; Bone age; Bone biomarkers; Bone mineral density